2022
DOI: 10.54268/baskara.5.1.95-107
|View full text |Cite
|
Sign up to set email alerts
|

Sukuk Linked Wakaf For MSME Develpoment

Abstract: The existing Sharia investment products are incorrect; the other is a state sukuk product. Aside from receiving returns on state sukuk, investors can also contribute to the country's development. Because the development of sukuk products is channeled to the actual sector, particularly for MSME (Micro, Small Maedium Enterprise) actors, Islamic financial institutions must play a role in carrying out the process of developing and aiding MSMEs. If many state sukuk products were previously allocated for infrastruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…This diagram summarizes the research approach used in research methodology related to CWLS in the scientific literature. It can be concluded that in the realm of research on CWLS, the dominant prevalence was found in the form of qualitative investigations in the form of literature studies with a percentage of 64.71% Afrianti, 2022;Anindhita et al, 2022;Armen et al, 2022;Cahyono et al, 2022;Hafandi et al, 2021;Indra et al, 2020;Istikomah et al, 2021;Lailatullailia et al, 2021;Maesarach et al, 2022;Mudriqoh, 2023;Mukti et al ., 2022;Nugroho et al, 2022;Puspitasari et al, 2022;Putri et al, 2020;Rahayu et al, 2020;Rahman et al, 2021;Maulina, 2022;Sa'idaturrohman , ;Sasongko et al, 2021;Siswantoro, ;Sulaeman et al, 2022;Tanjung & Agus, 2021 ;Ubaidilaah & Wahyu, 2021;Winarto et al, 2021; ANP (Afifah et al, 2022 ;Rabbani et al;Suratman et al, 2023) (Nurjamil, 2021), content analysis (Wati et al, 2022) and SLR Joseph, 2022).…”
Section: Cluster 4: Cwls Research Methodology (Additional)mentioning
confidence: 99%
“…This diagram summarizes the research approach used in research methodology related to CWLS in the scientific literature. It can be concluded that in the realm of research on CWLS, the dominant prevalence was found in the form of qualitative investigations in the form of literature studies with a percentage of 64.71% Afrianti, 2022;Anindhita et al, 2022;Armen et al, 2022;Cahyono et al, 2022;Hafandi et al, 2021;Indra et al, 2020;Istikomah et al, 2021;Lailatullailia et al, 2021;Maesarach et al, 2022;Mudriqoh, 2023;Mukti et al ., 2022;Nugroho et al, 2022;Puspitasari et al, 2022;Putri et al, 2020;Rahayu et al, 2020;Rahman et al, 2021;Maulina, 2022;Sa'idaturrohman , ;Sasongko et al, 2021;Siswantoro, ;Sulaeman et al, 2022;Tanjung & Agus, 2021 ;Ubaidilaah & Wahyu, 2021;Winarto et al, 2021; ANP (Afifah et al, 2022 ;Rabbani et al;Suratman et al, 2023) (Nurjamil, 2021), content analysis (Wati et al, 2022) and SLR Joseph, 2022).…”
Section: Cluster 4: Cwls Research Methodology (Additional)mentioning
confidence: 99%
“…Therefore, this is an excellent opportunity for Malaysian insurance companies to market and diversify their products in Turkey, and generally around the world (Media, 2014). According to Maesarach (2019), the development of the modern insurance industry is very fast in line with the needs of society. This is because companies that run the insurance industry are companies that manage forms of risk based on sharia principles.…”
Section: Malaysian Investment In Turkeymentioning
confidence: 99%
“…This value is sufficient to finance social development projects such as mosques or schools. Maesarach et al (2022) examined the growth of state sukuk and the form of sukuk product development through state CWLS for MSME development. Existing Islamic investment products are not right; one of them is the state sukuk product.…”
Section: Cluster 4 : Msme Development and Cwlsmentioning
confidence: 99%